Identification of pyrrolo[2, 3-d]pyrimidines as potent HCK and FLT3-ITD dual inhibitors. Issue 22 (15th November 2017) - Koda, Yasuko; Kikuzato, Ko; Mikuni, Junko; Tanaka, Akiko; Yuki, Hitomi; Honma, Teruki; Tomabechi, Yuri; Kukimoto-Niino, Mutsuko; Shirouzu, Mikako; Shirai, Fumiyuki; Koyama, Hiroo
Graphical abstract: Identification of HCK and FLT3-ITD dual inhibitors. Abstract: A series of novel pyrrolo[2, 3- d ]pyrimidines were synthesized by introducing 15 different amino acids to 7-cyclohexyl-5-(4-phenoxyphenyl)-7 H -pyrrolo[2, 3- d ]pyrimidine-4-amine. Compounds with potent activities against HCK and FLT3-ITD were evaluated in viability studies with acute myeloid leukemia cell line MV4-11. Our structure activity relationship analyses lead to the identification of compound31, which exhibited potent HCK and FLT3-ITD inhibition and activity against the MV4-11 cell line.